مدخل إلى أعمال برنارد شو - عثمان محمد جلال; العلي بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The 19th century witnessed immense events covering social, political, philosophical, and economic spheres. Scientific discoveries contradicted religious beliefs, and a lot of reformist movements and revolutionary theories were formulated. In such an eventful atmosphere, Bernard Shaw came to play his role as a sage of a social message. After joining the Fabian Society, Shaw started to shape his own conceptions about reforming society, and about the art of a vital and provocative drama through which he could preach his ideas. His task as a dramatist was to uncover the reality of social injustice, religious misconception and political farce. Thus, his plays dealt with serious themes that hardly left any aspect of life untouched. He wrote plays about real human problems such as war, religious intolerance, revenge, middle-class morality, in addition to calling for a new religion of “Creative Evolution” motivated by the “Life Force” to pave the way for the coming of the “Superman”. Finally, Shaw’s skilful handling of aestheticism and ambivalence in many of his plays was perfectly employed in order to produce very satisfying and interesting dramatic art. شهد القرن التاسع عشر أحداثا هائلة شملت مجالات اجتماعية وسياسية وفلسفية واقتصادية. وقد تضاربت المكتشفات العلمية مع المعتقدات الدينية وتشكلت العديد من الحركات الإصلاحية والنظريات الثورية. جاء برنارد شو إلى هذا الجو المليء بالأحداث لكي يقوم بدوره كرسول للإصلاح الاجتماعي. بعد انضمامه إلى " المجتمع الفابي " بدأ شو يكون مفاهيمه حول إصلاح المجتمع وحول فن الدراما الحيوية والمحرضة والتي يستطيع من خلالها أن يبشر بأفكاره. كانت مهمته بوصفه مسرحيا تقوم على كشف واقع الظلم الاجتماعي والمفاهيم الدينية الخاطئة والخداع السياسي. لذا عالجت مسرحياته المواضيع الجادة التي لم تترك مظهراً من مظاهر الحياة إلا وتناولته. كتب شو مسرحيات حول المشاكل الإنسانية كالحرب واللاتسامح الديني والانتقام وأخلاق الطبقة الوسطى. فضلا عن ذلك دعا شو إلى الدين الجديد المسمى بـ ": التطور الخلاق " الذي تدفعه " قوة الحياة " من أجل تمهيد الطريق لقدوم " الإنسان المتفوق ". وأخيراً فإن تناول شو الحاذق لعلم الجمال ومبدأ تضارب الأضداد في العديد من مسرحياته قد وظف بعناية فائقة من أجل الخروج بفن درامي مرضي وممتع في آن واحد.